Estimating Populations of Jaguar (Pantheraonca) in the Guanacaste Conservation Area, Costa Rica - Amit, Ronit (2009)
We estimated the jaguar population in two sites in Guanacaste Conservation Area (GCA), northwestern Costa Rica, using camera traps. We applied a capture -recapture method to obtain abundance and density was calculated for the effective sample area. For Sector San Cristobal the effective area was 164,81 km2, abundance was 9,50 ± 7,7 jaguars and density was 0,057 ± 0,046 ind/km2. For Santa Rosa and Guanacaste National Parks the effective area was 103,92 km2, abundance was 3,00 ± 2,46 jaguars for a density of 0,028 ± 0,023 ind/ km2. For the GCA, our results suggest that it is not possible to estimate the total number of jaguars because of the different population densities we found in two close areas. After the results of this study, we redesign a Jaguar Conservation Unit (JCU) proposed for northwestern Costa Rica, because of the probability that the Guanacaste Mountain Range presents a high jaguar density.